Jual Beli Online Dengan Menggunakan Sistem Dropshipping Menurut Sudut Pandang Akad Jual Beli Islam (Studi Kasus Pada Forum Kaskus) - Badrun (LPPM Institut Al-Ma'arif Way Kanan, 2020)
This study aims to examine the dropshipping system for buying and selling online (at the Kaskus forum). Regarding the advantages and disadvantages of the dropshipping system and its fiqh review. The higher level of technology and its use, now buying and selling online does not need to have to be face to face, with the internet, buying and selling becomes instant. Humans no longer need to go to the market or to shop to find the goods they want. By using an internet connection, ordering goods, making payments until the goods ordered arrived in front of the house can be done easily. Here the author emphasizes how this dropshipping system can be an opportunity for the community, especially for students who want to do business online without being bound by time and space and even capital. This research is a type of qualitative research. Emphasizing the quality or characteristics of the data experienced in accordance with descriptive understanding. Data collection by observation as an online buying and selling, then by studying the literature from various articles, books, news and literature that are seen as representing and related to the object of research. With the comparative analysis method, what happens in the field will be compared with the contract and fiqh law. The results showed that the online buying and selling system with the dropshipping system had similarities with the greeting agreement scheme and the wakalah contract. Dropshipping is a form of muamalah that is allowed.